2013
DOI: 10.1111/jcpp.12100
|View full text |Cite
|
Sign up to set email alerts
|

Biological and rearing mother influences on child ADHD symptoms: revisiting the developmental interface between nature and nurture

Abstract: Background Families of children with attention deficit hyperactivity disorder (ADHD) report more negative family relationships than families of children without ADHD. Questions remain as to the role of genetic factors underlying associations between family relationships and children’s ADHD symptoms, and the role of children’s ADHD symptoms as an evocative influence on the quality of relationships experienced within such families. Utilizing the attributes of two genetically sensitive research designs, the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
177
0
4

Year Published

2016
2016
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(204 citation statements)
references
References 35 publications
23
177
0
4
Order By: Relevance
“…For instance, Keown [40] found that more intrusive parenting behavior at age four predicted more ADHD symptoms in home-reared children; and Harold and colleagues [41], in a study with adopted children, reported that maternal negative behavior, which included intrusive parenting, was significantly linked to more ADHD symptoms at age 6. Also important to consider is GXE evidence that home-reared children homozygous for the 5-HTTLPR s allele have more attentional deficits when exposed to more negative parenting behavior, including intrusive behavior, than other children [42,43].…”
Section: Current Studymentioning
confidence: 99%
“…For instance, Keown [40] found that more intrusive parenting behavior at age four predicted more ADHD symptoms in home-reared children; and Harold and colleagues [41], in a study with adopted children, reported that maternal negative behavior, which included intrusive parenting, was significantly linked to more ADHD symptoms at age 6. Also important to consider is GXE evidence that home-reared children homozygous for the 5-HTTLPR s allele have more attentional deficits when exposed to more negative parenting behavior, including intrusive behavior, than other children [42,43].…”
Section: Current Studymentioning
confidence: 99%
“…Familial confounding could be explained by passive, evocative and active gene-environment correlations (rGE) (158,196). Evocative rGE is of little importance in the case of severe maltreatment (physical or sexual abuse) according to Jaffe et al (160,197), but may be relevant in corporal punishment (160) and hostile parenting style (161). Based on previous findings we assumed that abuse would be less influenced by genetic factors and more likely be due to idiosyncratic events in children' lives.…”
Section: Can Environmental Risks Causally Contribute To Adhd?mentioning
confidence: 99%
“…children with high verbal cognitive abilities will go to the library more often, or children with high novelty-seeking traits will more often expose themselves to potentially dangerous situations, increasing risk for injury). Passive rGE has been identified as a mechanism in the intergenerational transmission of externalizing behaviours (including ADHD and SUD) (159), whereas evocative rGE may play a role in corporal punishment in conduct disorder (160), as well as in the association between hostile parenting style and ADHD symptoms (161). Rutter (154) also described several other forms of gene-environment interplay, such as gene-environment interactions, epigenetic effects of environmental risks, as well as variations in heritability according to environmental circumstances.…”
Section: Gene-environment Interplaymentioning
confidence: 99%
“…Psychosocial risks, such as low income, family adversity and harsh/hostile parenting, whilst robustly causal for certain psychiatric disorders, are also correlates rather than proven causes of ADHD. Longitudinal studies, 59 treatment trials 60 and a study of children adopted away at birth 61 suggest that observed negative mother-child relationships (even in unrelated mothers) arise as a consequence of early child ADHD symptoms (reverse causation) and improve with treatment. However, exposure to very severe, early social deprivation appears to be different and causal.…”
Section: Environment and Gene-environment Interplaymentioning
confidence: 99%